Pengaruh Populasi Cacing Tanah dan Jenis Media Terhadap Kualitas Pupuk Organik - SUCIPTA, NI KOMANG SUCI PRASTIWI; KARTINI, NI LUH; SONIARI, NI NENGAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.4, No.3, Juli 2015, 2015)
ABSTRACT The Effect of Population and Media Type on the Quality of Organic Fertilizer The research was conducted in the soil Laboratory, of Agroecotechnology Department/Study Program, Faculty of agriculture, Udayana University on January to April 2014. The purpose of this study is to know the influence of earthworm populations and types of media on the quality of organic fertilizers. The materials used in the study of household waste (vegetable), cow dung, elephant dung and earthworms. The design of the study is randomized block design factorial. Treatment consisted of 16 combinations treatment, each combination was repeated 3 times so that became 48 treatments. The first factor consisted of cow dung media, elephant dung, vegetable waste mixed cow dung and vegetable waste mixed elephant dung. The second factor is earthworms population consisted of 10, 20 and 30. The results of the interaction treatment study showed significant effect to highly significant to : C/N ratio, earthworm population, organic-C, total-N, the population of the earthworm eggs and the total population microorganisms. Instead of variable P, and pH. The best quality of organic fertilizer in this study is cows dung and 20 earthworms seen from the earthworm population, the number of worm eggs, and P-available.   Keywords : earthworms, the type of media, organic fertilizer